"Das ist eine Wortschatzübung, die mir gefällt" – Faktoren der Attraktivität von Wortschatzübungen aus der Sicht von DaF-Lernenden - Targońska, Joanna (Linguistik Online, 2014)
as well as enumerated were the arguments indicating the appropriateness of making use of lexical exercises during a lesson of a foreign language. What is more, presented were the theoretical considerations upon the subject of factors affecting the effectiveness of the exercises used. In the empirical part presented was the research conducted in a sample group of 96 learners of German as a foreign language. In the research in question highlighted were the factors affecting the attractiveness of lexical exercises. Based on the subjective evaluations of attractiveness of particular lexical exercises, made by learners, distinguished were 11 categories of factors having an influence on the fact that a given lexical task is perceived by the sample group as motivating and attractive. On the basis of the factors isolated here it was possible to draw attention to the subjective theories on the part of the sample group pertaining to the process of learning vocabulary during a foreign language lesson and using lexical exercises.